(untitled) (Revista Científica Compendium, 2023)
The general objective of this research was to analyze the strategic marketing applied by the commercial company KRS Export C.A. in Barquisimeto during the year 2023. It is a descriptive, cross-sectional, documentary-based field study. The analyses were oriented to the external and internal environment of the business using evaluation tools – external factors evaluation matrix, competitive profile matrix and marketing audit. A survey structured according to the marketing mix and segmentation variables was applied to the organization´s customers. According to the analysis conducted, the organization has weaknesses in its corporate identity statement and in the areas of marketing, digital communication and infrastructure. Regarding the variables: product, price and distribution, the organization has successful strategies. The strategic guidelines established are aimed at developing alliances with telecommunication corporations, which will allow to diversify the product portfolio and revenues, as well as permanently monitor the competition.